Enhancing Sustainability and Economics of Concrete Production through Silica Fume: A Systematic Review - Ayedh Mohammad Alhajiri; Mohammad Nadeem Akhtar (Civil Engineering Journal, 2023)
This review article addresses the problems associated with the carbon footprint of the cement industry. The PRISMA framework methodology was for data extraction from published studies. In-depth research has been done in the literature on using silica fume as a cement replacement in concrete production, considering environmental, engineering, and economic (EEE) factors. The strength, durability, and economic parameters results revealed a positive variation of up to 5–20% substitution of silica fume. However, most past studies reported the threshold at a 10% replacement ratio. A novel benefit-cost ratio analysis was also done in this review study. The benefit-cost ratio analysis reveals the economically beneficial effects that can be achieved in sustainable silica fume-based concrete with a (5–20%) silica fume combination. The benefit-cost ratio showed positive effects, up to 20% cement replacement with silica fume. Hence, the higher cement replacement with silica fume is also beneficial in terms of the benefit-cost ratio. Further research has been proposed based on the findings of this review study. Doi: 10.28991/CEJ-2023-09-10-017 Full Text: PDF